Blood glutamate scavenging as a novel glutamate-based therapeutic approach for post-stroke depression. (February 2020) - Gruenbaum, Benjamin F.; Kutz, Ruslan; Zlotnik, Alexander; Boyko, Matthew
Post-stroke depression (PSD) is a major complication of stroke that significantly impacts functional recovery and quality of life. While the exact mechanism of PSD is unknown, recent attention has focused on the association of the glutamatergic system in its etiology and treatment. Minimizing secondary brain damage and neuropsychiatric consequences associated with excess glutamate concentrations is a vital part of stroke management. The blood glutamate scavengers, oxaloacetate and pyruvate, degrade glutamate in the blood to its inactive metabolite, 2-ketoglutarate, by the coenzymes glutamate–oxaloacetate transaminase (GOT) and glutamate–pyruvate transaminase (GPT), respectively. This reduction in blood glutamate concentrations leads to a subsequent shift of glutamate down its concentration gradient from the blood to the brain, thereby decreasing brain glutamate levels. Although there are not yet any human trials that support blood glutamate scavengers for clinical use, there is increasing evidence from animal research of their efficacy as a promising new therapeutic approach for PSD. In this review, we present recent evidence in the literature of the potential therapeutic benefits of blood glutamate scavengers for reducing PSD and other related neuropsychiatric conditions. The evidence reviewed here should be useful in guiding future clinical trials.